Pengaruh waktu Penyalaan Terhadap Kinerja Spark-Ignation Engine Berbahan Bakar LPG - Perpustakaan UGM, i-lib ([Yogyakarta] : Jurusan Perikanan Fak. Pertanian UGM, 2003)
In the present research, the effects of ignition timing on poformance of a LPG fueled spark-ignition engine have been experimentally examined. The research was conducted by introducing an LPG conversion kit in a gasoline engine test bed. Variations of brake torque, power, air-fuel ratio, and specific fuel consumption on engine speed (rotations per minute) were measured at several ignition timings. The present results show the maximum torque and power of the LPG -fueled engine are 20-30% lower than those of the gasoline fueled engine. It is identified that the mixture of LPG and air in the LPG fueled engine is too lean, so that the flame speed is lowered. To increase the performance of the LPG-fueled engine, the ignition timing needs to be advanced than the standard ignition timing of the gasoline fueledengine.